RADIO CHANNEL LORA IN THE ALARM SYSTEM - Кучеров, Дмитро Павлович; Березкін, Андрій Леонідович (Science-based technologies, 2019)
The article substantiates the importance of using security and warning means for the construction of perimeter security for “large” industrial facilities, such as oil refineries and metallurgical plants, military depots and bases, nuclear power plants and other strategic facilities based on new principles for constructing a radio channel, which is considered more preferable for large areas protection and satisfies all-weather condition. Since the radio channel is exposed to radio interference, the use of the Internet of things using LoRa radio-protocol is proposed as a new approach, where it is assumed to use broadband signals, namely, signals with linear-frequency modulation in packet mode. The analysis is based on the assumption of the additivity of the reception of a useful signal against a background of Gaussian noise with a zero mean, which allows interference and noise to be presented as a single interference signal. The packet mode of information transmission is analyzed in terms of the probability of errors in the packet and throughput. The dependences of the probability of a bit error on the packet length for various signal-to-noise ratios and types of binary phase modulation are established, which makes it possible to extend these relations to the chirp - signals. Relations are also obtained for an effective mechanism for transmitting a stream with repetition under conditions of information loss and an estimate of the channel capacity is given. Estimates are provided of the information transmission distance for a real radio channel for a transmitter-receiver based on the LoRa module constructed on the SX1276 chip. The range of the radio channel was estimated taking into account the predicted transmission and reception losses, and it was also estimated based on the real sensitivity of the transmitter-receiver, for which the Vvedensky formula was essentially used. The obtained relations are confirmed by modeling.